EARLY READING AND WRITING LEARNING STRATEGIES FOR CHILDREN WITH DISABILITIES IN INCLUSIVE ELEMENTARY SCHOOLS - Khairunnisa Khairunnisa; Sari Sari; Aris Sugianto (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
Early reading and writing skills are essential foundations of literacy, including for children with disabilities (CWD) in inclusive schools. This study aims to describe the strategies, media, and assessments applied in teaching early reading and writing for CWD in first grade at SDN Banua Anyar 8 Banjarmasin. A naturalistic qualitative approach was employed with eight participants, consisting of a classroom teacher, three special education assistants, and five CWD diagnosed with mild to severe autism. Data were collected through interviews, observations, and documentations, and analyzed using Miles and Huberman’s model. The results indicate that teaching strategies were adapted to the students’ characteristics, such as the TEACCH method for students with severe autism and cooperative or game-based learning for those with mild autism. Instructional media included posters, flashcards, pictures, puzzles, and videos, while assessments were individualized, ranging from simplified reading tasks to recognition of letters and numbers. These findings highlight the significance of individualized approaches, visual-audio media, and flexible assessments to enhance early literacy among CWD. The study implies fostering more responsive and meaningful inclusive literacy practices.